​​CRISPRi mediated investigation of the vulnerability of two essential cell wall biosynthetic gene products in mycobacteria. - Mahlakwana, Gugulethu Boreadi (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.